Conclusion of a JVS Forum: Refute the World Bank’s Ganges Strategic Basin Assessment Report - Gautam, Upendra (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
No abstract available DOI: http://dx.doi.org/10.3126/hn.v11i0.7171 Hydro Nepal Vol.11 2011 pp.77